Some thoughts on five Mycenaean terracotta figurines from the collection of the Museum of Fine Arts in Budapest - Árvai, Mirtill (Dissertationes Archaeologicae, 2026)
The Collection of Classical Antiquities of the Museum of Fine Arts, Budapest, (hereafter MFAB) holds five terracotta figurines attributed to the Mycenaean culture: a Psi (T.737), a Kourotrophos (T.15), a female figurine sitting on a throne (T.5), a Linear Type 2 bovine figure of (93.15.A), and a figure of a couple lying on a bed (T.13). This paper presents these figurines and discusses some questions regarding their typology, function, context, and origin.